ECO HOUSE PADA PERKEMBANGAN RUMAH TRADISIONAL BALI STUDI KASUS: DESA ADAT MENGWI, BADUNG - Widja, I Made (Jurnal Natah; Vol. 2, No. 1 Februari 2004, 2012)
Eco-house is an environment friendly house that is utilizing optimally the potential of local natural thus it is longed for both a thrifty and economical house, even cheap on its development process and a thrifty energy on its operation as well. The Balinese Traditional House Rumah is essentially categorized as the eco house seen intern of: its integrity on environment, the arrangement of the buildings unit, the use of land, the attention on environment, the use of material, natural energy, and the other natural resources as well. Nowadays, the Balinese Traditional House has rapidly developed to the modern affect, it is perhaps caused by: the population growth, the influence of modern and global, the change of employment, the land agriculture and the change of the house to shopping facilities. Formerly, it was very rarely to demolish the house fence to be store or shop area. But now it is effortless to detect the number of store/shop at house resident in particular residents who live at barrier of the main road. Its development has become intensely to be overcome, how the eco house could be seemingly applied on the development of Balinese Traditional House? Could it be revealed as the house that is both friendly environment and thrifty energy? The answer are: the eco house on development of Balinese Traditional Bali at Desa Adat Mengwi has been far away left and become barely to finding out the house that is thrifty energy and friendly environment at Desa Adat Mengwi.
Keywords: eco house, thrifty energy, friendly environment.